Content validation of the Quality of Life Inventory—Disability. (21st June 2019) - Epstein, Amy; Williams, Katrina; Reddihough, Dinah; Murphy, Nada; Leonard, Helen; Whitehouse, Andrew; Jacoby, Peter; Downs, Jenny
Abstract: Background: Focus is shifting to better understand the lived experiences of children with intellectual disability in relation to their quality of life (QOL). Yet no available QOL measures are grounded in the domains important for this population. We previously conducted qualitative parent caregiver interviews identifying QOL domains in children with intellectual disability to constitute a new measure of QOL. This study describes the content validity of the Quality of Life Inventory—Disability (QI‐Disability), a parent‐report measure developed for children with intellectual disability. Methods and Results: Questionnaire items were extracted from a qualitative dataset of 77 parent caregiver interviews. To establish content validation, a draft of QI‐Disability was administered to 16 parent caregivers of children with intellectual disability (Down syndrome, Rett syndrome, cerebral palsy, or autism spectrum disorder). Parents participated in a cognitive interviewing procedure known as the "think‐aloud" method. The process of item generation, cognitive debriefing, and refinement of QI‐Disability prior to its pilot testing are described. A conceptual framework is presented. Conclusions: Satisfactory content validity is reported, where ongoing consumer feedback shaped the dataset from which the final items were selected. Use of QI‐Disability for children with intellectual disability will allow for greater insight into service utility and targeted intervention.